Potential role of dew in enhancing productivity of mustard (Brassica juncea L.) in semi-arid regions of India - KUMAWAT, ANITA; SINGH, A.K.; KUMAR, ASHOK; RASHMI, I.; KALA, S. (Journal of Soil and Water Conservation, 2023)
Dew is a non-conventional and additional source of moisture which can alter the plant water balance by reducing leaf temperature, suppressing transpiration through evaporative cooling, and enhanced leaf albedo and emissivity and thus help to improve agronomic productivity under arid and semi-arid agroecologies. However, the significant role of dew in enhancing the agronomic yields of crops is the most neglected aspect in both arid and semi-arid agro-ecosystems. This study is about the dew accumulation and its significant contribution in improving productivity of mustard (Brassica juncea L.) during the dry rabi season, especially under rainfed conditions. The average dew accumulation was 22.8% higher than the average seasonal rainfall. The grain yield of mustard was 1.5 and 1.8 t ha-1 under rainfed and irrigated condition, respectively which is acceptable because of the saving of inputs and production cost by Rs. 5000-6000 ha-1. Thus, dew has a scope to improve the yield of crops besides enhancing fallow land utilization and augmenting income of the farmers in medium deep black soils of arid and semi-arid regions of India.